2011
DOI: 10.3923/pjbs.2011.142.145
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Drinking Water from Dispensers in Roadside Restaurants of Bangladesh

Abstract: The microbiological status of water from dispensers in different roadside restaurants of Dhaka city and Savar area was analyzed in this study. Seven samples from Dhaka and 8 samples of Savar were checked. The heterotrophic plate count was in a range of 1.0 x 10(3) CFU mL(-1) to 2.0 x 10(4) CFU mL(-1) (from new bottles), 1.0 x 10(3) to 1.5 x 10(4) CFU mL(-1) (after dispensation), and 1.5 x 10(3) CFU mL(-1) to 1.0 x l0(5) CFU mL(-1) (from serving glass). In several of the samples, the heterotrophic plate count w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The samples were found to contain gram negative bacteria like E. coli, Shigella spp., Klebsiella spp., Enterobacter spp., Pseudomonas spp., and Salmonella spp., which are potential pathogens and thus pose a serious threat to public health (Moniruzzaman et al, 2011).Although coliform organisms may not always be directly related to the presence of fecal contamination, the presence of coliforms in water suggested the potential presence of pathogenic enteric microorganisms such as Salmonella sp., Shigella sp., and Vibrio cholerae (Zamberlan da Silva et al, 2008). According to WHO (Anonymous, 2006), the bacteria that pose a serious disease risk whenever present in drinking water include Salmonella sp., pathogenic E. coli and Vibrio cholerae.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were found to contain gram negative bacteria like E. coli, Shigella spp., Klebsiella spp., Enterobacter spp., Pseudomonas spp., and Salmonella spp., which are potential pathogens and thus pose a serious threat to public health (Moniruzzaman et al, 2011).Although coliform organisms may not always be directly related to the presence of fecal contamination, the presence of coliforms in water suggested the potential presence of pathogenic enteric microorganisms such as Salmonella sp., Shigella sp., and Vibrio cholerae (Zamberlan da Silva et al, 2008). According to WHO (Anonymous, 2006), the bacteria that pose a serious disease risk whenever present in drinking water include Salmonella sp., pathogenic E. coli and Vibrio cholerae.…”
Section: Resultsmentioning
confidence: 99%
“…Although the presence of faecal coliform in water supply may not be harmful, but it is an indication of the presence of faeces [49] . Despite cases of water vending machines contaminated by faecal coliforms (E. coli O157:H7) [50] , fortunately, none of the selected subjects in this study was found to harbour faecal coliform (Figure 1, Table 3). However, in accordance to other studies [51,52] ,the presence of other total coliform (eg.…”
Section: Bacterial Colonies On Hicrome Tm Coliform Agarsmentioning
confidence: 66%
“…In an another study, from 2014, the heterotrophic bacterial load was shown above the acceptable limits in drinking water, significantly higher in water dispenser samples than tap water samples [20]. Moniruzzaman et al 2011 carried out a study about the microbiological contamination (heterotrophic bacteria, Escherichia coli, Pseudomonas sp., and Salmonella sp.) in water samples dispensed in road-side restaurants compared to water samples from the bottle before dispensing [21].…”
Section: Introductionmentioning
confidence: 99%
“…Moniruzzaman et al 2011 carried out a study about the microbiological contamination (heterotrophic bacteria, Escherichia coli, Pseudomonas sp., and Salmonella sp.) in water samples dispensed in road-side restaurants compared to water samples from the bottle before dispensing [21]. In Italy, Liguori et al 2010 andSacchetti et al 2014 conducted studies to compare the microbial quality of water dispensers and municipal tap water [2,9].…”
Section: Introductionmentioning
confidence: 99%